Tourism Clustering as a Factor of Regional Economic Growth: Structural Features of a Regional Cluster - Ukhina, Tatiana; Shafazhinskaya, Natalia; Panikarova, Nadezhda; Kovaleva, Agata; Ryakhovsky, Dmitriy (Anais Brasileiros de Estudos Turísticos, 2022)
The cluster model is crucial for developing tourism. Such clusters enable the economic development of any region and the whole country and increase the competitiveness of the final product in the market and the production activities of enterprises included in the clusters. This is especially relevant for the tourism industry, which is a promising area of economic development. Therefore, it is significant to study the possibilities and experience of implementing the cluster model in further research. The study aims at determining and analyzing the main structural features of the regional tourism cluster. Based on an expert survey, the article determines and considers the main structural features of the regional tourism cluster as exemplified by the existing regional tourism clusters in Russia. It is concluded that the main structural feature of a regional tourism cluster is its structural connectivity which provides participants with an advantage over competitors acting separately.